The Feasibility Study of Constructing Wind Power Plants in the North of Sistan and Baluchestan Province from a Climatological and Environmental Point of View - Azizoallah Goharnia; Mahmood khosravi; Mohsen Hamidianpour (کاوش‌های جغرافیایی مناطق بیابانی, 2019)
Iran is the most populated country in the Middle East. As a part of its development plans, it needs to increase its energy resources and  specifically invest in renewable energies. Wind, as one of the sources of renewable energy, has a special place in this regard. This is due to the geography and topography of the country. In this study, the fuzzy system analysis process was used to weigh climatological and environmental variables on the purpose of determining suitable locations for building a wind power plant in the north of Sistan and Baluchestan province. The environmental variables were evaluated based on their influence and importance in the site selection process. The results showed that the north of the province can be categorized into four locations where wind farms can be established. They include locations with excellent (7142.45 Km²), good (1304.12 Km²), average (1635.65 Km²) and low potentials (6388.29 Km²). As the findings suggest, depending on the arrangement of 100 KW wind turbines, 307106 turbines can be installed in the region. The investment return period was calculated and found to be six years and seven months.